الشیخ ابو حماد نصیر احمد کی تفسیر ایضاح القرآن کے امتیازات وخصائص کا ایک تجزیاتی مطالعہ: Al-Sheikh Abu Hamad Nasir Ahmad Tafseer Izah al-Qur'an Its Distinguishing and characteristics: An analytical Study - Muhammad Imran Khan,; Dr. Badshah Rehman,; Dr. Najmul Hasan, (Al Manhal Research Journal, 2024)
Allah has revealed the Holy Qur'an to Prophet Muhammad ﷺ which is a great source of guidance for all mankind till the Day of Resurrection. The first commentator of the Holy Qur'an is the Prophet ﷺ. After him ﷺ, the Companions of the Prophet, the Tabi'in, the Taba'i Tabi'in and other scholars performed interpretation services. And this series will continue till the doomsday. The name of Al-Sheikh Abu Hamad Nasir Ahmad is also included in the list among the commentators of the present era. Al-Sheikh Abu Hamad Naseer Ahmed bin Muhammad Saeed was born on February 24, 1970 at Khal Zor Mundi District in Lower Dir Khyber Pakhtunkhwa. He received his early education from his father, Sheikh Muhammad Saeed. Allah has exalted Al-Sheikh Abu Hamad Naseer Ahmad in both contemporary and religious sciences. He has written many books, among which his great book is Tafsir called Izah al-Qur'an. This is a hand written commentary so it is still a work in progress. Although the end is near. The commentator has collected many sciences in it. It has many advantages and features. These are: interpreting the Qur'an with the Qur'an, interpreting the Qur'an with the Hadith, and interpreting the Qur'an with the sayings of the Companions, with the sayings of the Tabi'in and with Arabic rules and interpreting the Qur'an according to the relevant words. In summary, this Tafsir has been written in the light of the Qur'an, hadiths, companions, tabi'een, and Arabic rules. In this Tafsir, his personal opinion has been completely avoided. Modern jurisprudential issues have been explained very well. Apart from this, Arabic grammar has also been used in this Tafsir. In addition, the Qur,anic sciences have been described in this Tafsir. Therefore, this Tafsir is the best and original means of solving the requirements of the present age. This can benefit both the public and private sector. May Allah bless Sheikh Abu Hamad Naseer Ahmed with long life and may Allah accept his great effort. Amen.